BACTERIOLOGICAL PROFILE OF BACTERIAL MENINGITIS AT TERTIARY CARE HOSPITAL IN NORTH KARNATAKA. - DR RAVINDRANATH GANGANE; DR PRAVEEN KUMAR DODDAMANI (International Journal of Pharma and Bio Sciences, 2013)
Bacterial meningitis is a serious health problem requiring early diagnosis, effective treatment & prophylaxis. It remains a major cause of high mortality in India and other developing nations. This study was conducted in our institute to know the bacteriological profile of bacterial meningitis and study the antibiotic susceptibility pattern of isolated organisms. 308 CSF samples were collected from clinically diagnosed cases of Bacterial meningitis. CSF was centrifuged, first culture media were inoculated and followed by procedures like direct wet mount, Grams stain, Negative staining, ZN staining. For culture CSF was inoculated on Blood agar, McConkeys Agar, chocolate Agar, BHI broth and sabouraud’s dextrose Agar. Identification of bacteria was done by various biochemical tests, enzymatic tests and agglutination test with specific antisera.Identification of fungal cultures done by grams stain, negative staining and lacto-phenol cotton blue mount.Antibiotic sensitivity done by Kirby-bauers disc diffusion test using mueller Hinton agar according to standard guidelines. Detection MRSA was done according to CLSI guidelines. Out of 308 samples, 82 showed aerobic bacterial growth,10 fungal growth and 11 smears were AFB positive. Most common age group affected was 16 to 60yrs, male were affected more when compared females with male female ratio of 1.75:1 Most common isolate was streptococcus pneumonia 26(31.7%), others were Klebsiella 17(20.7%), E.coli 10(12.1%), Psedumonas aeurginosa 8(9.7%), Staphylococcus aureus 6(07.3%) ,proteus 5(6.09%),H.influenza 3(3.6%),acinetobacter2(2.4%),N.meningitidis,2(2.4%),enterococci fecalis 2 (2.4%) citrobacter frundii 01(3.7%) each. Bacterial meningitis is an emergency condition where early diagnosis and aggressive treatment plays vital role in decreasing mortality rate. Most common isolate was streptococcus pneumonia in adults and E.coli in patients less than 1yr.emergence of multidrug resistant organisms in recent times makes the early diagnosis of meningitis important factor to reduce mortality and morbidity associated with it.